Multimodal Approach in Online EFL Class Using Islamic Learning Materials: Students' Perspective - Djamdjuri, Dewi Suriyani; Suseno, Muchlas; Tajuddin, Shafruddin; Lustyantie, Ninuk; Chaeruman, Uwes Anis (Universitas Negeri Makassar, 2021)
This study aims to find out how students' perspectives on learning English use 21st century learning strategies through a multimodal approach to teaching English for EFL students. A lecture was conducted online for one semester (four months) by using Islamic topics as learning materials. The learning materials were presented and discussed, then students were asked to write or talk about the topics. This study uses a descriptive qualitative approach to data collection through the provision of questionnaires and interviews with 47 students of the Islamic Broadcasting Program at the Faculty of Islamic Religion at a private Islamic university in Bogor, Indonesia, in the English language course. From the data collected through a set of questionnaires, it can be concluded that, 1) the majority of respondents are interested in using Islamic materials to learn English; 2) the majority of respondents state that Islamic materials assisted them in improving their English language skills; 3) The majority of respondents are interested in using online Islamic resources. Furthermore, respondents stated that the multimodal approach to learning is very interesting, very good, and can help them to learn English. In addition, students wished that direct interaction between lecturers and students could continue to function well. Hence, the use of multimodal-based materials could provide interactive opportunities between lecturers and students.Â